The impact of the COVID-19 pandemic on the non-bank loan market in Poland - Waliszewski, Krzysztof (Wpływ pandemii COVID-19 na rynek pożyczek pozabankowych w Polsce, 2020)
The article presents the impact of the COVID-19 pandemic on the non-bank loan market in Poland. Data from the Credit Information Bureau for the period 2019-2020 provided to the author, included the number and value of loans granted by lending institutions, broken down into amount ranges (up to PLN 1,000, over PLN 1,000 to up PLN 5,000, over PLN 5,000). The COVID-19 pandemic had a negative impact on the loan market due to the decline in demand for this type of products and a reduction in lending due to the tightening of anti-usury regulations generally regarding the maximum non-interest cost of credit introduced under the anti-crisis shield. Additionally, lowering the interest rates by the NBP influenced the maximum interest charged by these entities. As a consequence, some entities ceased their activity and some changed their business profile to pawnshops. The following research methods were used in the article: analysis of the available literature, legal acts, and statistical data from BIK
Financial Sciences. Nauki o Finansach, 2020, vol. 25, no. 4, s. 66-74
Keywords: COVID-19; pandemic; non-bank loans; consumer protection; pandemia COVID-19; pożyczki pozabankowe; ochrona konsumenta